Dermoscopy of pilomatricoma: A case report with a review of the literature - Radia Chakiri; Youssef Bouhajeb (Our Dermatology Online, 2022)
Pilomatricoma is a benign tumor originating from hair follicle matrix cells and characterized by the presence of cutaneous and subcutaneous nodules up to 3.0 cm in diameter, usually on the head, neck, and upper extremities, rarely on the trunk and lower extremities. An eleven-year-old female with a painless, erythematous-purplish tumor of the back. A dermoscopic examination revealed irregular linear vessels, white structures, and structureless grayish-blue areas. Histological examination after excision confirmed the diagnosis of pilomatricoma. Dermoscopy may be a useful tool for improving the clinical recognition of pilomatricoma.